2002
DOI: 10.1152/ajpendo.00054.2002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of muscle insulin-like growth factor I expression by tumor necrosis factor-α

Abstract: The role of TNF-alpha in muscle catabolism is well established, but little is known about the mechanisms of its catabolic action. One possibility could be that TNF-alpha impairs the production of local growth factors like IGF-I. The aim of this study was to investigate whether TNF-alpha can directly inhibit IGF-I gene and protein expression in muscle. First, we investigated whether the acute inflammation induced by endotoxin injection changes IGF-I and TNF-alpha mRNA in rat tibialis anterior muscle. Endotoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 62 publications
4
60
2
Order By: Relevance
“…However, it has been reported (Foulstone et al 2001) that the effects of IGF-I on muscle may depend on the cytokine environment in such a way that in the presence of TNF-a, IGF-I induces apoptosis. The increase in IGF-I gene expression in skeletal muscle of arthritic rats does not correlate with the decrease observed in the muscle of lipopolysaccharide (LPS)-treated rats (Lang et al 2000, Fernández-Celemín et al 2002 and fasting rats (Dehoux et al 2004). The increase in MuRF-1 and MAFbx gene expression found in the skeletal muscle of arthritic rats (Granado et al 2005) has also been found in the muscle of LPS-injected rats (Dehoux et al 2003).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, it has been reported (Foulstone et al 2001) that the effects of IGF-I on muscle may depend on the cytokine environment in such a way that in the presence of TNF-a, IGF-I induces apoptosis. The increase in IGF-I gene expression in skeletal muscle of arthritic rats does not correlate with the decrease observed in the muscle of lipopolysaccharide (LPS)-treated rats (Lang et al 2000, Fernández-Celemín et al 2002 and fasting rats (Dehoux et al 2004). The increase in MuRF-1 and MAFbx gene expression found in the skeletal muscle of arthritic rats (Granado et al 2005) has also been found in the muscle of LPS-injected rats (Dehoux et al 2003).…”
Section: Discussionmentioning
confidence: 92%
“…It has been postulated that TNF-a exerts its catabolic effects in skeletal muscle in a paracrine/autocrine manner (Fernández-Celemín et al 2002). Therefore, the gene expression of E3 ubiquitin ligases MuRF-1 and MAFbx in the muscle of arthritic rats was not changed after PEG-sTNFRI administration probably as a consequence of the lack of effect of this protein complex on muscular TNF-a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A difference between the short-and long-term effect could be at least partly explained by the changes in receptor function and/or ligand binding, with transient increasing expression of TNF-R1 leading to enhanced protein synthesis, followed by induction of feedback loops, such as the secretion of soluble TNF-R, which sequesters the cytokine [26]. Alternatively, a decrease in autocrine IGF-I production [13,42] could blunt the increase in protein synthesis. The TNF-α concentration effective in causing a decrease in IGF-I-stimulated glucose uptake and protein synthesis can be considered as physiological, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The receptors specific for TNF-α, IL-1, IL-6 and IFN-γ are expressed in the skeletal muscle and myogenic cells at a low level, but their contents have been shown to increase noticeably after the induction of inflammation and treatment with a mixture of cytokines in vitro [12], suggesting the existence of local mechanisms enhancing the skeletal muscle response to cytokines. The mechanisms of the catabolic effect of cytokines in the skeletal muscle may involve: a modulation of the activity of the hormones controlling protein metabolism [6]; the inhibition of the production of anabolic factors [13]; and the regulation of the expression of other cytokines [14]. In recent years, there has been a hypothesis regarding hormones and cytokines, which may mutually modulate biological effects via common intracellular signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%